2021
DOI: 10.3390/nano11030587
|View full text |Cite
|
Sign up to set email alerts
|

Composite Structure Based on Gold-Nanoparticle Layer and HMM for Surface-Enhanced Raman Spectroscopy Analysis

Abstract: Hyperbolic metamaterials (HMMs), supporting surface plasmon polaritons (SPPs), and highly confined bulk plasmon polaritons (BPPs) possess promising potential for application as surface-enhanced Raman scattering (SERS) substrates. In the present study, a composite SERS substrate based on a multilayer HMM and gold-nanoparticle (Au-NP) layer was fabricated. A strong electromagnetic field was generated at the nanogaps of the Au NPs under the coupling between localized surface plasmon resonance (LSPR) and a BPP. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The interference of the molecules that contribute to adsorption can prevent the detection of target molecules. The plasmon band moves from the visible region for spherical AuNPs to the NIR by changing the size, shape, and level of aggregation [ 259 ].…”
Section: Applicationsmentioning
confidence: 99%
“…The interference of the molecules that contribute to adsorption can prevent the detection of target molecules. The plasmon band moves from the visible region for spherical AuNPs to the NIR by changing the size, shape, and level of aggregation [ 259 ].…”
Section: Applicationsmentioning
confidence: 99%
“…Second, the MHMM is an excellent sensing platform capable of coupling with other plasmon resonances to generate novel phenomena. Recently, it has been reported that the modification of nanoparticles on a MHMM acting as a 2D grating enabled the coupling of BPP and LSPR to generate an extremely strong electric field between the nanoparticles, 48,49 which is very useful for biomolecular detection.…”
Section: Excitation Of the Bpp Mode In Mhmm By Grating Couplingmentioning
confidence: 99%
“…Usually, they exhibit average effects of the electromagnetic response of the medium. One branch of metamaterials is hyperbolic metamaterials (HMMs), which comprise layered metal-dielectric structures [ 17 , 18 , 19 , 20 ]. HMMs can show high anisotropic properties, owing to the presence of the opposite components of effective electric tensors.…”
Section: Introductionmentioning
confidence: 99%